Peran Guru Dalam Meningkatkan Mutu Kegiatan Belajar Mengajar di Era Sistem Informasi pada Boarding School Tri Sukses Generus Kota Balikpapan - Muhaeni, Budi; Yuliwulansih, Haryani; Siampa, Vindy Nugraha; Utami, Reski; Gladys, Febrina; Avianti, Astri; Pratiwi, Hanameyra; Nabila, Dea; Sikki, Nurhaeni (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Boarding School is an alternative form of education that combines formal student education in schools and strengthening religious character in Islamic boarding schools [1]. Tri Sukses Generus Boarding School, Balikpapan City also does the same thing, which is emphasized by its vision: Having Good Morals, Being Alim-Faqih, Being Independent Based on Religious Professionalism, Science and Technology and Having Environmental Insight This study aims to analyze the role of teachers in improving the quality of teaching and learning activities in the information system era. In collecting data, researchers used observation, interview and document analysis methods to understand existing phenomena, such as manual management of student learning outcomes, unmeasurable student progress, and less integrated reporting. This study concludes that the implementation of an integrated learning information system can support the analysis of academic, non-academic, and administrative data, thereby increasing the effectiveness of education management. Therefore, it is recommended that Tri Sukses Generus Boarding School develop an information system according to the needs that have been identified, provide training to teachers to improve digital competence, and conduct periodic evaluations of the implementation of the information system.